2008
DOI: 10.1007/s11199-008-9474-7
|View full text |Cite
|
Sign up to set email alerts
|

Body Dissatisfaction in Adolescent Boys and Girls: Objectified Body Consciousness, Internalization of the Media Body Ideal and Perceived Pressure from Media

Abstract: The aim of the present study was to examine a theoretical model describing the relationships between body shame and body surveillance (components of objectified body consciousness), internalization of the media body ideal, perceived pressure from media, body mass index and body dissatisfaction in Swiss adolescent boys and girls. A sample of 819 boys and 791 girls aged 14-16 years completed selfreport measures of the mentioned concepts. As expected, girls had higher body shame and body surveillance than boys. S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
134
1
10

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(166 citation statements)
references
References 49 publications
21
134
1
10
Order By: Relevance
“…During the adolescence period, when a significant body transformation takes place and the body gains feminine or masculine attributes, girls' and boys' preoccupation with their own body becomes very intense (Smolak, 2004). Its most common effect is dissatisfaction with one's external appearance, which can be experienced as dissatisfaction with oneself (Eisenberg et al, 2006;Knauss et al, 2008;Presnell et al, 2004). There is a risk that the process of identity shaping will be dominated by the processes of shaping the silhouette and external looks (Markey, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…During the adolescence period, when a significant body transformation takes place and the body gains feminine or masculine attributes, girls' and boys' preoccupation with their own body becomes very intense (Smolak, 2004). Its most common effect is dissatisfaction with one's external appearance, which can be experienced as dissatisfaction with oneself (Eisenberg et al, 2006;Knauss et al, 2008;Presnell et al, 2004). There is a risk that the process of identity shaping will be dominated by the processes of shaping the silhouette and external looks (Markey, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For Swiss male adolescents in seventh through twelfth grade, Knauss et al (2008) found that pressures from the media to lose weight was related to increases in internalization of the physical lean and muscular ideal. Amongst male undergraduates, social pressures from family members and the media to have a muscular and lean body were associated with internalization of a lean and muscular physical ideal (Tylka, 2011).…”
Section: Social Weight Pressures and Internalizationmentioning
confidence: 99%
“…Researchers have demonstrated that social weight pressures are associated with higher levels of internalization in boys (e.g., Knauss, Paxton, & Alsaker, 2008;Rodgers, Ganchou, Franko, & Chabrol, 2012;Tylka, 2011). For Swiss male adolescents in seventh through twelfth grade, Knauss et al (2008) found that pressures from the media to lose weight was related to increases in internalization of the physical lean and muscular ideal.…”
Section: Social Weight Pressures and Internalizationmentioning
confidence: 99%